PENGARUH KINERJA KEUANGAN, GROWTH OPPORTUNITY DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL (STUDI PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI, MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2016-2017) - Eka Indah Wahyu; Ronny Malavia Mardani; M. Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to determine the relationship of financial performance, growth opportunity, and firm size on the mod structure. The type of research used is explanatory. The data used is secondary data, which is obtained by documentation techniques, namely by searching and collecting annual report data obtained from the website. The population in this study is a food and beverage costumer goods company that Is listed on the Indonesia stock exchange for the period 2016-2017, which is 18 companies and the sample used is 18 companies.The data analysis techbique in this study used the normality test, classic assumption test, multiple linear regression test and hypothesis test. The measuring instrument used in measure financial performance such as likuidity (current ratio) and protability is Return On Asset (ROa/ROI), for growth opportunity uses the results of the difference for the difference in total t-years asset and total asset t-1, and to measure capital structure using a debt to equity ratio.The results of this analysis indicate that: (1) profitability has a negative effect on capital structure, (2) likuidity has a negative effect on capital structure,: (3) firm size has a negative effect on capital structure, while (4) growth opportunity has a positive effect on capital structure.Keywords : Dividend Policy, Capital Structure, Interest Rates, and Firm Value.